Property rights, collective action, and agroforestry - Place, Frank; Otsuka, Keijiro; Scherr, Sara J. (International Food Policy Research Institute, 2004)
In this brief, we explore the role that social institutions -specifically property rights and collective action - may play in the development of agroforestry.... In the future, property rights and collective action will play increasingly pivotal roles in defining rights and responsibilities over the externalities of tree management practices. As stakeholders recognize the need for effective management of, for example, the erosion resulting from tree felling or rights to carbon sequestration from tree planting, they will increasingly value and depend on the institutions that protect their property rights. -- from Text.